2020
DOI: 10.2174/1381612826666200708133912
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Ischemic Stroke: Role of Oxidative Stress

Abstract: : Stroke is the second leading cause of mortality and the major cause of adult physical disability worldwide. The current available treatment to recanalize the blood flow in acute ischemic stroke is intravenous administration of tissue plasminogen activator (t-PA) and endovascular treatment. Nevertheless, those treatments have the disadvantage that reperfusion leads to a highly harmful reactive oxygen species (ROS) production, generating oxidative stress (OS), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
160
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(203 citation statements)
references
References 0 publications
2
160
0
2
Order By: Relevance
“…Подвергнутые ишемии различной степени выраженности нейроны, клетки нейроглии и эндотелиальные клетки сосудов головного мозга переносят воздействие внутриклеточных метаболических нарушений, сдвига ионного баланса и осмотического статуса, летальной деполяризации, кальциевой перегрузки, образования свободных радикалов и других токсичных соединений, иммунной реакции с элементами аутоиммунитета, эксайтотоксичных медиаторов [31][32][33][34][35][36][37].…”
Section: основные звенья развития ишемического поврежденияunclassified
“…Подвергнутые ишемии различной степени выраженности нейроны, клетки нейроглии и эндотелиальные клетки сосудов головного мозга переносят воздействие внутриклеточных метаболических нарушений, сдвига ионного баланса и осмотического статуса, летальной деполяризации, кальциевой перегрузки, образования свободных радикалов и других токсичных соединений, иммунной реакции с элементами аутоиммунитета, эксайтотоксичных медиаторов [31][32][33][34][35][36][37].…”
Section: основные звенья развития ишемического поврежденияunclassified
“…Peroxisome is an organelle where very long chain fatty acids (>C22) are metabolized [ 10 , 11 ]. Although ROSs act as important signal molecules, in general, ROSs are regarded to play detrimental roles in cell injury [ 9 , 12 , 13 , 14 ]. Thus, several intrinsic protective mechanisms operate to reduce the toxic effects of ROSs in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several intrinsic protective mechanisms operate to reduce the toxic effects of ROSs in the brain. The dysfunction of these intrinsic mechanisms by which the brain eliminates ROSs leads to both acute [ 9 , 12 , 13 , 14 ] and chronic [ 15 , 16 ] neuronal damage. In ischemic stroke, for example, the elimination of ROSs during reperfusion therapy by either pharmacological thrombolysis or a mechanical thrombectomy is an essential therapeutic strategy, since damaged mitochondria during ischemia serve as a potential source of massive ROS production, especially after reperfusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, an epidemiological survey indicated that strokes, with an incidence of 136.64 per 100,000 individuals, had replaced cancer as the leading cause of mortality in China ( 5 ). At present, intravenous thrombolytic therapy is the main clinical treatment for ischemic stroke ( 1 , 6 ), and there is still a lack of effective drugs to protect neurons from death. Therefore, there is a need for multi-target and improved therapeutic drugs, which is why the beneficial effects of Traditional Chinese Medicine (TCM) is worth investigating ( 7 ).…”
Section: Introductionmentioning
confidence: 99%